Epidemiological situation of bovine and bubaline tuberculosis in the state of Pará, Amazon region of Brazil - Oliveira, Bruno Cesar Ribeiro da Silva; Oliveira, Jefferson Pinto; Pinho, Ana Paula Vilhena Beckman; Dias, Ricardo Augusto; Grisi Filho, José Henrique Hidebrand; Gonçalves, Vitor Salvador Picão; Heinemann, Marcos Bryan; Amaku, Marcos; Telles, Evelise Oliveira; Ferreira, Bruno Fontana Soares; Ferreira, Fernando; Ferreira Neto, José Soares (Frontiers in Veterinary Science, 2024)
IntroductionBovine tuberculosis is one of the primary infectious diseases affecting cattle. Although several countries have managed to eradicate this zoonosis it remains endemic and uncontrolled across many countries in Africa, Asia, Latin America, and the Middle East. Brazil launched its national control and eradication program in 2001, and since then, epidemiological studies have been carried out to define optimal control strategies and to enable the management of the process in each region.MethodsThis study covered the state of Pará, which was divided into three regions, in each of which a pre-established number of properties were randomly selected, and within each property, a minimum number of animals were drawn to be tested by the tuberculin test to classify the farm as infected or free of the disease. A questionnaire was administered to the selected properties to identify the risk factors for the disease.ResultsA total of 976 properties comprising 17,151 animals were tested. The prevalence of infected properties in the regions ranged from 3.1% [1.3; 4.9] to 18.6% [14.3; 22.9], while tuberculin-positive animals ranged from 0.24% [0.09; 0.40] to 4.8% [2.4; 7.3]. The introduction of cattle untested for bTB and the renting of pastures have been identified as risk factors for the disease in this state.DiscussionPará has one of the highest prevalences of bovine tuberculosis in Brazil, and the implications of these results for public health were discussed. We therefore proposed that the state’s Official Veterinary Service, together with the private dairy and meat sectors, pursue the objective of controlling or eradicating the disease, along with mechanisms to verify its effectiveness. The differences between the two objectives were discussed, but in both cases, an education program is necessary to inform cattle and buffalo breeders that they need to test animals for tuberculosis before introducing them to their farms, and also to avoid renting pastures for cattle to graze and rest while moving on foot, as these practices have contributed the most to the spread of bTB in the state.